2007
DOI: 10.1253/circj.71.1885
|View full text |Cite
|
Sign up to set email alerts
|

Activity Monitoring in Heart Failure Patients With Cardiac Resynchronization Therapy

Abstract: xercise intolerance is a hallmark of heart failure (HF) and is predictive of all-cause mortality and hospitalizations. 1,2 Discouraging a sedentary lifestyle and promoting physical activity have both been shown to improve functional capacity, quality of life, and clinical outcome. 3,4 Cardiac resynchronization therapy (CRT) restores the cardiac electro-mechanical synchrony, leading to improved pumping function in HF patients with ventricular conduction disturbances. Consequently, CRT is able to increase func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…As expected, D‐PA was lowest immediately after device implantation and increased substantially over the next 90 days . After 90 days, some studies showed that activity levels remained stable, whereas other studies described a continued increase in D‐PA for up to 6 months after implantation . Interpretation of these findings is complicated by the variation in how and when baseline activity was determined.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…As expected, D‐PA was lowest immediately after device implantation and increased substantially over the next 90 days . After 90 days, some studies showed that activity levels remained stable, whereas other studies described a continued increase in D‐PA for up to 6 months after implantation . Interpretation of these findings is complicated by the variation in how and when baseline activity was determined.…”
Section: Resultsmentioning
confidence: 81%
“…D‐PA data are increasingly being used to understand patterns of activity engagement after ICD implantation; however, investigators have varied in the approach taken to calculate the baseline level of D‐PA, making it difficult to compare findings across studies. In some studies, baseline is defined as average activity over a period of several days, 1 to 2 weeks after CIED implantation, to account for procedural recovery time; in other studies, baseline is defined as average activity over 7 to 30 days, 1 to 2 months after implantation . Despite this variation in approach, D‐PA at baseline is consistently low across studies (<3 hours of total activity per day), regardless of device manufacturer or sample characteristics .…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies of accelerometer assessed activity in HF have been largely restricted to patients with HF and reduced EF (HFrEF) but have demonstrated correlations between variously quantitated accelerometer data and NYHA (14), 6MWD(12, 14), peak oxygen consumption (14, 15), estimated (Seattle Heart Failure Model) or observed mortality risks(16, 17), non-HF specific QOL questionnaires(18), therapeutic response to cardiac resynchronization(19, 20) and changes in clinical status(17, 21). Our findings document that accelerometer assessed activity is similarly associated with HF functional measures in HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown increases in accelerometer-assessed activity after cardiac resynchronization therapy, confirming its ability to reflect therapeutic response 41, 46, 47 . Validity, analytical issues, and compliance with externally worn accelerometer devices have been addressed in clinical trials for patients with COPD, among whom age and activity level are likely comparable to elderly patients with HFpEF 4851 .…”
Section: Assessment Of Symptom Burden In Hfmentioning
confidence: 77%